Penggunaan Youtube Sebagai Media Pembelajaran Al-Qur’an Dan Hadits Pada Peserta Didik Kelas V Madrasah Ibtidaiyah - Sutopo, Langgeng; Munawaroh, Munawaroh; Sari, Tri Maya (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2024)
Abstract This research aims to evaluate the effectiveness of using YouTube as a medium for learning the Al-Qur'an and Hadith for class V students at Madrasah Ibtidaiyah. This research includes qualitative research which is descriptive or an explanation of YouTube learning media, is field research, the collection method is divided into 3: Observation, Interview, Documentation. Data analysis techniques: Collection, Reduction, Conclusion. The research results show that using YouTube as a medium for learning the Al-Qur'an and Hadith can help the learning process, and can facilitate students in learning. By using YouTube media as a medium for learning the Koran and Hadith, students gain learning experiences that can increase motivation, independence and make students more active in learning. Based on this research, it is recommended that the use of YouTube as a medium for learning the Koran and Hadith can be applied more widely in learning at Madrasah Ibtidaiyah. It is also necessary to develop content that is more varied and in line with students' needs so that learning effectiveness can be further improved